Istikhdāmu Wasīlati Google Form fī Taqwīmi Taʿlīm Mahārat al-Kitābah bi Madrasah Dār al-Tawḥīd al-Mutawassiṭah Balung Jember: The Use of Google Forms as an Assessment Tool in Teaching Writing Skills at Dār al-Tawḥīd Islamic Junior High School, Balung, Jember - Abicandra, Muhammad Nidom Hamami; Nadzri, Ahmad Itsbat (Critical Review of English-Arabic World Journal, 2023)
كان تقويم تعليم مهارة الكتابة في هذا العصر له اعتماد كبير إلى التكنولوجيا. وجوجل فورم وسيلة على أساس الإنترنت يركز في التقويم والاستبيان. ويركز هذا البحث إلى استخدام جوجل فورم في تقويم تعليم مهارة الكتابة. ويهدف هذا البحث إلى وصف استخدام جوجل فورم في عملية تقويم تعليم مهارة الكتابة بالمدرسة دار التوحيد المتوسطة بالونج جمبر التي تشمل عدة المكونات هي خطوات التقويم ومشكلات عملية التقويم. استخدم الباحث المنهج الكيفي الوصفي من خلال البحث الميداني وجمع البيانات المستخدم بالملاحظة والمقابلة الشخصية والوثائقية ليحصل البيانات وتحليل البيانات في بهذا البحث بطريقة ميليس وهوبرمان. أما نتائج هذا البحث وهي (1) أن خطوات في عملية تقويم تعليم مهارة الكتابة تنقسم إلى نوعين وهما التخطيط والتنفيذ. التقويم التكويني يتعلق بالتقويم اليوم والأسبوعي والشهري والتقويم التحصيلي يتعلق ببتقويم منتصف الفصل الدراسي ونهاية الفصل الدراسي. و(2) وأما المشكلات في عملية تقويم تعليم مهارة الكتابة تنقسم إلى ثلاثة أنواع وهي مشكلات من المدرسة وهي تتعلق عن أحوال المرافق لعملية التعليم والتقويم ومشكلات من المعلم تتعلق عن قدرته ومهاراته في عملية التقويم وصعوبة في البداية بسبب عدم التدريبات. ومشكلات من الطلاب تتعلق عن قدراتهم ومهاراتهم جسديا ونفسيا وصعوبة االاستخدام بسبب شبكة الاتصال و عدم الكفاءة في استخدام الوسيلة.   The evaluation of teaching writing skills in this era relies heavily on technology. Google Forms is an internet-based tool that focuses on assessment and questionnaires. This research focuses on the use of Google Forms in evaluating the teaching of writing skills. The aim of this study is to describe the use of Google Forms in the evaluation process of teaching writing skills at Darut Tauhid Junior High School in Balung, Jember, which includes several components: evaluation steps and problems encountered in the evaluation process. The researcher used a descriptive qualitative method through field research, and data were collected using observation, interviews, and documentation to obtain data and analyze them using the Miles and Huberman technique. The results of the study are: (1) The steps in evaluating the teaching of writing skills are divided into two types, namely planning and implementation. Formative assessment includes daily, weekly, and monthly evaluations, while summative assessment includes mid-semester and end-of-semester evaluations. (2) The problems in evaluating the teaching of writing skills fall into three categories: problems from the institution, which relate to the condition of facilities for teaching and assessment; problems from the teacher, which relate to their abilities and skills in assessment and initial difficulties due to lack of training; and problems from the students, which relate to their physical and psychological abilities and skills, as well as difficulties in using the tool due to network issues and lack of proficiency in using the platform.